Survey method of health care providing to children less than one year in health ‎departments - zahra mokhtari; noshaz mir haghjo; shadman reza masuoleh; anooshirvan kazemnezhad (Guilan University of Medical Sciences, 2007)
Introduction: Health care providing to children with optimal quality is part of maternal and ‎child health program that its quality performance causes reduced mortality, complication and ‎health maintenance. Thus evaluating these care and promotion of health care providers, ‎performance and its quality certainly will have effective role in maternal child well – being‏.‏‎ ‎ Objective: This research aimed to determine method of health care providing to children less ‎than one year was done.‎ Methods: This study is a cross – sectional descriptive research and in this research ‎‏97‏‎ ‎employees of health centers were observed during offering health care to ‎‏291‏‎ infants specially ‎growth monitoring and vaccination. Health centers were selected through cluster sampling and ‎staff selected with census. Data collection tool was a questionnaire including two sections. ‎The first part included demographics completed by sample and second part included checklist ‎related to growth monitoring and vaccination completed through observation. Analysis of ‎data was done by descriptive statistics (Mean and Deviation) and deductive statistics (X‏2‏‎- test ‎and Pearson s correlation).‎ Result: Research finding about sample demographic characteristics showed that most of them ‎‎(‎‏%52/6‏‎) were between ‎‏35‏‎ – ‎‏44‏‎ and most of them (‎‏%92/8‏‎) didn t have a child under one year. ‎Most of them participated in re – education related to growth monitoring and vaccination and ‎most of them (‎‏%44/3‏‎) provided favorable health care related to vaccination and growth ‎monitoring.‎ Conclusion: Results showed that there was a significant correlation between age, children ‎educational course, studies, record of service in family health care unit and participation in re–‎education course with method of health care providing to children under one year related ‎growth monitoring and vaccination (P<‎‏0/001‏‎). But there was no significant correlation ‎between having child under one year and method of care provided to children under one year ‎‎(P<‎‏0/002‏‎). Thus most samples (‎‏%96‏‎) had favorable method in maintaining cold chain system.‎